Inter-communal migrations in Switzerland: a "mountain factor"? - Martin Camenisch; Bernard Debarbieux (Revue de Géographie Alpine)
To go beyond existing publications on inter-communal migrations in Switzerland, this paper focuses on a comparison of behaviours between communes of different types: rural, urban, mountain, tourist, etc. It is based on two sets of data: the Swiss Population Census (1999-2008) and the Swiss Household Panel. This paper has two main conclusions of this paper: first, contrary to the dominant practice which compares communes according to their respective difference between in-migration and out-migration rate, this paper highlights the contrast between “warm” and “cold” communes (comparing the migration rate itself); there is a "mountain factor" which means that most inter-communal migrations occur within the mountain zone, or within the Swiss Plateau.